Law Enforcement Against Religious Blasphemy on Social Media in Indonesia - Suprijati Sarib; Rai Iqsandri; Sabil Mokodenseho (Eastasouth Institute, 2023)
This study looks into the complex legal environment surrounding blasphemy enforcement on social media platforms in Indonesia, a country known for its wide range of religious and cultural practices. Using a thorough mixed-methods approach, the study combines technology evaluations, legal analyses, and sociological surveys to give a comprehensive knowledge of the prospects and problems in reducing online blasphemy. The legal analysis delves into the complexities of the Blasphemy Law and the Electronic Information and Transactions (EIT) Law, exposing obstacles in its implementation in the ever-changing digital landscape. Different public perspectives are captured through societal surveys, which highlight the influence of religion on attitudes and the efficacy of existing legislative measures. Technological evaluations explore the complexity of algorithms used for content moderation and the cooperation between law enforcement and platforms. Through the cross-analysis of these aspects, inequalities and links are shown, encouraging a nuanced conversation on striking a balance between religious sensitivity and freedom of expression. The study's conclusions highlight the necessity for a flexible and culturally aware strategy in dealing with online blasphemy and offer recommendations for legislators, law enforcement organizations, and technology stakeholders.